Preclinical delayed toxicity studies of BCMA CAR T-cell injection in B-NDG mice with multiple myeloma - Guo, Jianmin; Wu, Qiqi; Li, Hongjian; Liang, Chun; Dai, Jinlong; Zhang, Shuren; Dai, Cailing; Zhang, Jishuai; Wen, Yuying; Yang, Wei (Frontiers in Immunology, 2024)
Purpose Based on the efficacy data from the previous study of B-cell maturation antigen (BCMA) chimeric antigen receptor (CAR) T-cell injection, we further examined the delayed toxicity for 8 weeks after a single dose of BCMA CAR T-cell injection to observe possible toxic reactions. Methods B-NDG mice transplanted with multiple myeloma (MM) cells were given a single dose of BCMA CAR T-cell injection at two dosages or human normal T cells and then subjected to examinations including clinical signs, weight and food intake measurements, haematology, blood biochemical analysis, cytokine assay, T-lymphocyte subpopulation quantification and histopathology on days 28 and 56 after dosing. In addition, quantitative polymerase chain reaction (qPCR) was used to quantify DNA fragments in different tissues to assess the tissue distribution of CAR and provide a basis for its preclinical safety evaluation and clinical dosing. Results In the delayed toxicity study, no mortality or significant toxic effects such as reductions in food intake, body weight, relevant biochemical parameters and target organ weights were observed in the BCMA CAR T-cell-treated groups. Compared to the model group, restorative changes in clinical signs and clinicopathology indicating therapeutic effects were seen in the BCMA CAR T-cell-treated groups. Human-derived cytokines interleukin-2 (IL-2), IL-4, IL-6, IL-12, IL-10, tumor necrosis factor α (TNF-α), and interferon-γ (IFN-γ) could be detected in all cancer cell–bearing mice by cytokine level measurement. IFN-γ levels showed a geometric increase due to the graft versus host disease (GVHD) response induced in the mice, while the levels of the other cytokines did not show significant changes. Histopathological examination indicated that the BCMA CAR T-cell treatment groups showed mixed cellular infiltration of human-derived T cells, cancer cells, and inflammatory cells in several target organs including the liver, spleen, lung, and kidney, and some of them showed mild tissue damage, but the number of the animals and the severity of damage were significantly less than those of the T-cell control group as well as the model group. The results of the tissue distribution study showed that BCMA CAR T cells were mainly concentrated in the kidney, lung, bone marrow and the related immune organs/tissues, and the distribution of BCMA CAR T cells was highly consistent with that of MM cells, suggesting that BCMA CAR T cells could follow the cancer cells during metastatic targeting of the tissues. Conclusions The present study demonstrated a low toxicity of BCMA CAR T-cell injection, with manageable side effects and good anticancer activity and without observable adverse effects. This study provides data to support future clinical studies of BCMA CAR T-cell injection for MM.